Delli Aspetti de Paesi. Vecchi e nuovi Media per l'Immagine del Paesaggio: Tomo I. Costruzione, descrizione, identità storica - Alfredo Buccaro (Storia e iconografia dell'architettura, delle città e dei siti europei, 2018)
Starting from one of the most significant chapters of Leonardo's Libro di Pittura, we hwant to focus on the media - namely on the narrative, descriptive and graphics methodologies together with the techniques adopting during the modern and contemporary age as 'diffusers' of the landscape image - and on the deriving potential models for the enhancement of the historical landscape heritage.